Geographical Evidence and Social Imagination of Borders: 19th and 20th Century Literary and Artistic Representations of Borders Reflecting on the Work of Comenius - Řezníková , Lenka (Dějiny – teorie – kritika, 2013)
The topos of leaving into exile has been established in the 19th century as an integral part of biographies of Comenius. Scenes of ‘farewell to homeland’ became the subject of numerous literary and artistic representations, which stabilized, canonized, and gradually modified its basic components. They focused, among other things, on the border where the scene usually took place. The border tended to be depicted as an administrative and geographical institution, one that was to the exiles-to-be not only semantically significant but also clearly recognizable. Upon closer examination of texts and visual artefacts, however, it turns out that in a number of representations, all geographic evidence is notably absent and rather just simulated by narrative suggestions.